The evolution of music and human social capability - Schulkin, Jay; Raglan, Greta B. (Frontiers in Neuroscience, 2014)
Music is a core human experience and generative processes reflect cognitive capabilities. Music is often functional because it is something that can promote human well-being by facilitating human contact, human meaning, and human imagination of possibilities, tying it to our social instincts. Cognitive systems also underlie musical performance and sensibilities. Music is one of those things that we do spontaneously, reflecting brain machinery linked to communicative functions, enlarged and diversified across a broad array of human activities. Music cuts across diverse cognitive capabilities and resources, including numeracy, language and space perception. In the same way, music intersects with cultural boundaries, facilitating our “social self” by linking our shared experiences and intentions. This paper focuses on the intersection between the neuroscience of music, and human social functioning to illustrate the importance of music to human behaviors.